Innovation in crisis of business spaces: High demand from companies in the second most important port in Peru. - Mosqueira Atalaya, Yeison Cleidin; Urrutia Nuñez, Ruth Seleny; Rodríguez Castañeda, Yessenia Nathalí (LACCEI, 2024)
Abstract–Paita is considered an industrial city where the second most important port in Peru is located, which is why the most important national and international manufacturing companies in the country are located in this city, promoting economic development and exporting to different national and international markets. However, this important province lacks business infrastructure that can help companies remain competitive and adopt new technologies. For this reason, this research has a mixed qualitative and quantitative approach, carried out through a statistical analysis of the business condition of the city, which shows alarming results and a high demand for companies, so it is considered convenient to evaluate the possibility of a solution proposal through the proposal of a business center with certain characteristics and considering some cities that had the same problem. Finally, the main conclusions are compiled, where the statistical data justify the need for business development spaces.